Is it time for a new classification of mast cells? What do we know about mast cell heterogeneity?. Issue 1 (12th February 2018) - Frossi, Barbara; Mion, Francesca; Sibilano, Riccardo; Danelli, Luca; Pucillo, Carlo E. M.
Summary: Mast cells (MCs) are derived from committed precursors that leave the hematopoietic tissue, migrate in the blood, and colonize peripheral tissues where they terminally differentiate under microenvironment stimuli. They are distributed in almost all vascularized tissues where they act both as immune effectors and housekeeping cells, contributing to tissue homeostasis. Historically, MCs were classified into 2 subtypes, according to tryptic enzymes expression. However, MCs display a striking heterogeneity that reflects a complex interplay between different microenvironmental signals delivered by various tissues, and a differentiation program that decides their identity. Moreover, tissue‐specific MCs show a trained memory, which contributes to shape their function in a specific microenvironment. In this review, we summarize the current state of our understanding of MC heterogeneity that reflects their different tissue experiences. We describe the discovery of unique cell molecules that can be used to distinguish specific MC subsets in vivo, and discuss how the improved ability to recognize these subsets provided new insights into the biology of MCs. These recent advances will be helpful for the understanding of the specific role of individual MC subsets in the control of tissue homeostasis, and in the regulation of pathological conditions such as infection, autoimmunity, and cancer.